Profiling the Production of Antimicrobial Secondary Metabolites by Xenorhabdus khoisanae J194 Under Different Culturing Conditions - Booysen, Elzaan; Rautenbach, Marina; Stander, Marietjie A.; Dicks, Leon M. T. (Frontiers in Chemistry, 2021)
Species from the genus Xenorhabdus, endosymbiotic bacteria of Steinernema nematodes, produce a number of antibacterial and antifungal compounds, some of which are anti-parasitic. In this study, we report on the effect growth conditions have on the production of antimicrobial compounds produced by Xenorhabdus khoisanae J194. The strain was cultured in aerated and non-aerated broth, respectively, and on solid media. Production of antimicrobial compounds was detected after 24 h of growth in liquid media, with highest levels recorded after 96 h. Highest antimicrobial activity (350 mm2/mg) was obtained from cells cultured on solid media. By using ultraperformance liquid chromatography linked to mass spectrometry (UPLC-MS) and HPLC, the antimicrobial compounds PAX 7E and xenocoumacin 2 were identified. Eight xenoamicins were identified, of which four are considered novel. PAX 7E and xenocoumacin 2 were produced by cells cultured in non-aerated broth and on solid media. Production of antimicrobial compounds by X. khoisanae J194 may be regulated by oxygen, water activity, or both. A further 27 compounds were detected, of which six are novel with broad-spectrum antimicrobial activity. Based on these findings, X. khoisanae J194 produce a variety of antimicrobial compounds that may have application in disease control.